2003
DOI: 10.1046/j.1472-765x.2003.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of Aeromonas veronii biovar sobria as Vibrio alginolyticus by the Vitek system

Abstract: Aims: To find the cause of misidentification of aeromonads when using the Vitek system. Methods and Results: Two Aeromonas veronii biovar sobria isolates were misidentified as Vibrio alginolyticus by the Vitek system. Both strains' identification was confirmed by biochemical testing, API 20E/20NE kits and/or 16S RFLP analysis. Thirty-one known Aeromonas species were tested by the Vitek system using 0AE45 and 0AE85% saline in the suspension medium. It was not clear whether low salinity causes misidentification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 11 publications
2
29
0
1
Order By: Relevance
“…The tendency of miniaturized biochemical identification systems to confuse Aeromonas isolates with Vibrio isolates noticed in our study was already known (2,19). In our case, MicroScan misidentified eight isolates (10.8%) as Vibrio fluvialis, results similar to those reported by Vivas et al (21).…”
supporting
confidence: 81%
“…The tendency of miniaturized biochemical identification systems to confuse Aeromonas isolates with Vibrio isolates noticed in our study was already known (2,19). In our case, MicroScan misidentified eight isolates (10.8%) as Vibrio fluvialis, results similar to those reported by Vivas et al (21).…”
supporting
confidence: 81%
“…The few contradictory results obtained by conventional biochemical tests and multiplex PCR assay in respect of A. hydrophila were analyzed in detail. There were reports that biochemical confirmation at times lacks specificity for some strains of bacterial pathogens (Park et al 2003;Beaz-Hidalgo et al 2010) and it need not be the same for all species. In this work, four isolates of A. hydrophila biochemically confirmed did not show the presence of hemolysin gene, ahh1 in the multiplex PCR assay.…”
Section: Resultsmentioning
confidence: 99%
“…Some other authors have also reported poor results from the API systems and discrepancies with traditional tube testing when identifying Aeromonas strains isolated from fish (Godoy et al, 2010;Han et al, 2011;Joseph & Carnahan, 1994;and references therein). Some methods may even misidentify Aeromonas strains as Vibrio species (Park et al, 2003;Soler et al, 2003b). To avoid this confusion, Chacón and colleagues designed a specific probe based on a fragment of the glycerophospholipid-cholesterol acyltransferase (GCAT) gene that is able to hybridize with all Aeromonas species but not with strains from other genera .…”
Section: Phenotypic Identification With Conventional Methods and Minimentioning
confidence: 99%
“…the "A. hydrophila" complex (including A. hydrophila, A. bestiarum and A. salmonicida and also latter A. popoffii), the "Aeromonas caviae" complex (including A. caviae, A. media and A. eucrenophila) and "Aeromonas sobria" complex (including A. sobria, A. veronii, A. jandaei and A. trota) (Abbott et al, 1992;2003;Borrell et al, 1998;Kozińska et al, 2002;Martin-Carnahan & Joseph, 2005;Martínez-Murcia et al, 2005). In the descriptions of new Aeromonas species, the mandatory criteria of identifying differential phenotypic tests from other existing Aeromonas species has been fulfilled (Figueras et al, 2011b and references therein).…”
Section: Phenotypic Identification With Conventional Methods and Minimentioning
confidence: 99%
See 1 more Smart Citation